A Review of Boys Love Manga and Beyond. History, Culture, and Community in Japan: Boys Love Manga and Beyond. History, Culture, and Community in Japan, Edited by Mark Mclelland, Kazumi Nagaike, Katsuhiko Suganuma and James Welker, University Press of Mississippi, 2015. 304 pages, 6 × 9 inches, 42 b&w illustrations, ISBN: 978-1-62846-119-0. Issue 1 (21st December 2016) - Flowers, Tiffany A.
Abstract : This book review provides a brief overview of the collection Boys Love Manga and Beyond: History, Culture, and Community in Japan, edited by Mark Mclelland, Kazumi Nagaike, Katsuhiko Suganuma and James Welker (University Press of Mississippi, 2015 ). The review offers a summary of the main topics covered in the collection, and discusses its strengths, weaknesses and implications for other academic fields from the perspective of a scholar specializing in Education, Children's Literature, Literacy and Diversity.